Efforts to Increase the Competitiveness of Export Products in the Free Market in Islamic Economic Development - Robby Prasetyo Kusjiarsih; Hendri Hermawan Adinugraha; Morse Kathryn (Sharia Oikonomia Law Journal, 2023)
This research intends to increase the competitiveness of export products on the free market in Islamic economic development. This study uses a systematic literature review method. The data source for this research comes from journals and other literature related to direct marketing. The findings in this literature review study conclude that the realization of free trade tends to encourage each country to fully specialize in the production of goods that have a comparative advantage for that country. The readiness of a country in globalization depends on how the country encourages the products it produces to have a comparative advantage. With comparative advantage, competitive products will be produced in the global market. In addition, with the growth of world trade areas, which tend to form trading blocs in almost all continents, adding to the globalization of trade in the world today. Economic globalization is the expansion of global markets where global resources in production and marketing are no longer limited by geographic boundaries of countries. In fact, globalization covers a wider field, including the influence of politics, technology and culture. The role of the market becomes more important in creating economic conditions than the government. Countries can have a way that is considered most appropriate, but it is market policy that will be directly related to global markets. Companies and other forms of organization are no longer limited by national territory, the world has truly become one global "village".